Bioactive potentials of sulfated polysaccharides isolated from brown seaweed Sargassum spp in related to human health applications: A review. (August 2018) - Sanjeewa, K.K. Asanka; Kang, Nalae; Ahn, Ginnae; Jee, Youngheun; Kim, Young-Tae; Jeon, You-Jin
Abstract: Genus Sargassum is a group of edible brown seaweeds, which are an important component of Korean, Chinese, and Japanese cuisines. In addition, Sargassum spp also play an important role in the tropical sea water eco-systems. Other than as a food source, recent studies have shown that Sargassum spp are a rich source of novel bioactive compounds. Among the isolated bioactive components, sulfated polysaccharides (SPs) have gained considerable attention due to their proven health benefits. Also, a number of publications have shown promising health effects of SP isolated from this brown seaweed. However, industrial range utilization of the SP from brown seaweeds are limited due to the lack of collective information about the SP collected from brown seaweeds. Therefore, in the present review attempts were made to discuss the bioactive properties of SPs separated from genus Sargassum in relation to human health improvement applications. Furthermore, anticoagulant, antioxidant, anticancer, antibacterial and antiviral activities of SPs from genus Sargassum were reviewed to update current information on these valuable natural components. Thus, information in this paper might be useful to fill the knowledge gap between research studies and industrial application. Graphical abstract: Image 1 Highlights: Bioactive properties of sulfated polysaccharides separated from Sargassum spp. Fucoidan is one of the bioactive sulfated polysaccharides present in Sargassum spp. Future applications of fucoidan isolated from Sargassum spp as a functional material.